Computer performance engineering : 13th European Workshop, EPEW 2016, Chios, Greece, October 5-7, 2016, Proceedings /: 13th European Workshop, EPEW 2016, Chios, Greece, October 5-7, 2016, Proceedings. (2016) - Unknown
No abstract available